(untitled) (LACCEI, 2024)
The objective is to analyze the quality management system focused on socio-technical characteristics and principles in a company dedicated to providing advisory services to improve its performance. The results of the diagnosis demonstrated that exists social aspects to improve, in which we can apply socio-technical principles such as compatibility, limit specifications, and information fluidity, wherefore, implementing socio-technical aspects was proposed modular empowerment and autonomy, compatibility, limit specifications, fluid information, support congruence, consciousness – awareness, enrichment, and job sharing, time limitations, multifunctionality, action – research, which, are expected to reduce the human resources expenses, and improve sales, productivity, and market acceptance, and therefore generate a sustainable business for the company.